Critical Issues in Mycobiota Analysis - Halwachs, Bettina; Madhusudhan, Nandhitha; Krause, Robert; Nilsson, R. Henrik; Moissl-Eichinger, Christine; Högenauer, Christoph; Thallinger, Gerhard G.; Gorkiewicz, Gregor (Frontiers in Microbiology, 2017)
Fungi constitute an important part of the human microbiota and they play a significant role for health and disease development. Advancements made in the culture-independent analysis of microbial communities have broadened our understanding of the mycobiota, however, microbiota analysis tools have been mainly developed for bacteria (e.g. targeting the 16S rRNA gene) and they often fall short if applied to fungal marker-gene based investigations (i.e. internal transcribed spacers, ITS). In the current paper we discuss all major steps of a fungal amplicon analysis starting with DNA extraction from specimens up to bioinformatics analyses of next-generation sequencing data. Specific points are discussed at each step and special emphasis is placed on the bioinformatics challenges emerging during operational taxonomic unit (OTU) picking, a critical step in mycobiota analysis. By using an in silico ITS1 mock community we demonstrate that standard analysis pipelines fall short if used with default settings showing erroneous fungal community representations. We highlight that switching OTU picking to a closed reference approach greatly enhances performance. Finally, recommendations are given on how to perform ITS based mycobiota analysis with the currently available measures.